2011
DOI: 10.2478/s11658-010-0024-2
|View full text |Cite
|
Sign up to set email alerts
|

R proteins as fundamentals of plant innate immunity

Abstract: Abstract:Plants are attacked by a wide spectrum of pathogens, being the targets of viruses, bacteria, fungi, protozoa, nematodes and insects. Over the course of their evolution, plants have developed numerous defense mechanisms including the chemical and physical barriers that are constitutive elements of plant cell responses locally and/or systemically. However, the modern approach in plant sciences focuses on the evolution and role of plant protein receptors corresponding to specific pathogen effectors. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 107 publications
1
37
0
2
Order By: Relevance
“…Our study indicates that four primarily moderately conserved miRNAs, namely miR1510a*, miR1507, miR2678 (Szittya et al, 2008;Lelandais-Brière et al, 2009), and miR5213, regulate disease resistance genes. Plants have evolved a general defense response to biotic interactions involving toll and interleukin-1 receptor (TIR)/nucleotide-binding site-Leu-rich repeat disease resistance genes and PR proteins (Jones and Dangl, 2006;Głowacki et al, 2011). Although basal defense mechanisms, which include the accumulation of phenolic compounds and PR proteins, are activated upon the interaction with AM fungi (Campos-Soriano et al, 2010;Abdel-Fattah et al, 2011), we observed that mRNA levels of many of the miRNA-targeted disease resistance genes are decreased in mycorrhizal roots.…”
Section: Mirna*-mediated Target Cleavagementioning
confidence: 84%
“…Our study indicates that four primarily moderately conserved miRNAs, namely miR1510a*, miR1507, miR2678 (Szittya et al, 2008;Lelandais-Brière et al, 2009), and miR5213, regulate disease resistance genes. Plants have evolved a general defense response to biotic interactions involving toll and interleukin-1 receptor (TIR)/nucleotide-binding site-Leu-rich repeat disease resistance genes and PR proteins (Jones and Dangl, 2006;Głowacki et al, 2011). Although basal defense mechanisms, which include the accumulation of phenolic compounds and PR proteins, are activated upon the interaction with AM fungi (Campos-Soriano et al, 2010;Abdel-Fattah et al, 2011), we observed that mRNA levels of many of the miRNA-targeted disease resistance genes are decreased in mycorrhizal roots.…”
Section: Mirna*-mediated Target Cleavagementioning
confidence: 84%
“…Pathogens must circumvent or suppress this first-line surveillance mechanism in order to develop disease. On the other hand, some plant varieties also express a mechanism known as gene-for-gene resistance [4], which relies on the recognition of specific avirulence gene products from the pathogen by complementary R receptors. This recognition elicits a set of biochemical reactions, including generation of H 2 O 2 and reactive oxygen species (ROS), lipid peroxidation, ion fluxes, protein phosphorylation and phytoalexin synthesis, which are generally referred to as the Hypersensitive Response (HR) [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the preliminary transient transformation experiments in plant protoplasts, the fire fly luciferase reporter was used. For a different application, luciferase reporter can be substituted by the flg22 elicitor itself (Gómez-Gómez and Boller 2000; Zipfel and Felix 2005), or alternatively, by the resistance R protein genes known to induce the hypersensitive result which may lead to apoptosis (Glowacki et al 2010). Similar Gal4DBD-VP16-based transcriptional feedback loops were previously built by others for the expression of luciferase reporter in plants (Schwechheimer et al 2000), the amplification of cytotoxic diphtheria toxin A gene in mammalian cell lines (Imhof et al 2000), or in monitoring translation of the second coding region (feedback effector) within a dicistronic mRNA (Zhou et al 2005).…”
Section: Resultsmentioning
confidence: 99%